A modified water-based coating and its preparation method and application
By using silicone hybrid modified epoxy resin in aqueous epoxy coatings and acrylic modified polyurethane resin for mixing and adding hollow glass microbeads, the existing water-based epoxy coatings have been solved to improve adhesion, weather resistance, salt spray resistance and flash rust resistance, and the excellent performance and smoothness of the coating film are achieved.
Patent Information
- Application Number
- CN202310590798.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-05-24
AI Technical Summary
The existing water-based epoxy coatings have difficulties in improving adhesion, weather resistance, salt spray resistance and flash rust resistance, and the increased viscosity leads to uneven coating film.
The silicone hybrid modified epoxy resin was further mixed and modified with acrylic-modified polyurethane resin, and hollow glass microbeads with different particle sizes were added to the coating to improve the mechanical strength and anti-flash rust properties.
Excellent adhesion, weather resistance, salt spray resistance, solvent resistance and flash rust resistance after the water-based coating is formed, while avoiding the problem of uneven coating film caused by increased viscosity.
Smart Images

Figure BDA0004245440820000021 
Figure BDA0004245440820000081 
Figure BDA0004245440820000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water-based coatings, in particular to a modified water-based coating and a preparation method and application thereof. Background Art
[0002] Waterborne epoxy coatings play an important role in the field of industrial anti-corrosion coatings due to their excellent adhesion, resistance to neutral salt spray, and resistance to solvents. Traditional waterborne two-component epoxy coatings have poor weather resistance and generally cannot be used directly outdoors as topcoats, which limits the scope of application of epoxy coatings. The general method to improve the weather resistance of two-component epoxy coatings is to chemically modify them and introduce groups with excellent weather resistance into the epoxy molecules. Although this improves the weather resistance of the two-component epoxy coatings, its salt spray resistance is greatly reduced at the same time, making it difficult for the modified coatings to be used in heavy-duty anti-corrosion fields with high anti-corrosion requirements. At the same time, they have the disadvantages of long drying time and slow hardness building time, which makes them unable to meet the fast-paced construction requirements on site.
[0003] At present, most of the single-component epoxy coatings are modified to improve the weather resistance, salt spray resistance, solvent resistance and other properties of water-based epoxy coatings. For example, patent CN105131778A discloses a water-based mid-coat paint containing epoxy-organic silicone resin modified polyurethane-acrylic acid aqueous dispersion, which is to first prepare an organosilicon-modified epoxy resin prepolymer, and then add the organosilicon-modified epoxy resin prepolymer to a system containing acrylic monomer and polyurethane monomer for further polymerization to obtain a polymer dispersion with a cross-linked network structure. However, the presence of the cross-linked network structure will lead to an increase in coating viscosity, poor leveling, uneven coating, poor wetting effect of coating and substrate, and after curing and film formation, the adhesion to the substrate will be reduced. In order to ensure the adhesion of the coating to the substrate, the improvement of the performance of water-based epoxy coatings such as weather resistance, salt spray resistance and solvent resistance is limited.
[0004] In addition, due to the presence of water, water-based paint is prone to flash rust when applied on the surface of carbon steel substrates, especially at welds. The general solution is to add flash rust agents to inhibit the occurrence of flash rust, but the addition of flash rust agents will have a negative impact on the water resistance and salt spray resistance of the paint film, and it is difficult to take both into account.
[0005] Therefore, it is necessary to provide a water-based coating having good adhesion, weather resistance, salt spray resistance, solvent resistance and flash rust resistance. Summary of the invention
[0006] The purpose of the present application is to overcome the defects of existing waterborne epoxy coatings that adhesion and weather resistance, solvent resistance, salt spray resistance, and flash rust resistance cannot be taken into account at the same time, and to provide a modified waterborne coating. The coating of the present application is mainly composed of silicone hybrid modified epoxy resin, which is further mixed and modified with acrylic acid modified polyurethane resin, so that the coating has good adhesion, weather resistance, salt spray resistance, and solvent resistance after film formation; hollow glass microspheres with different particle sizes are also added, which can significantly improve the mechanical strength of the coating after film formation, and work together with the anti-rust pigment in the coating system to improve the anti-flash rust performance of the coating after film formation.
[0007] Another object of the present application is to provide a method for preparing the modified water-based coating.
[0008] Another object of the present application is to provide the use of the modified water-based coating in the preparation of containers, steel structures, mechanical equipment, and transportation vehicles.
[0009] To achieve the above objectives, this application adopts the following technical solutions:
[0010] A modified water-based coating comprises the following components in parts by weight:
[0011]
[0012] The average particle size D of the hollow glass microspheres is less than 40 μm, and the D 90 / D 50 It is 1.5 to 3.0.
[0013] The water-based coating of the present application is mainly composed of epoxy resin modified by organosilicon hybridization, which is further mixed and modified with polyurethane resin modified by acrylic acid, wherein: epoxy resin has the advantages of high modulus, high strength, strong adhesion, low molding shrinkage and good chemical resistance, and the hydroxyl and epoxy groups of epoxy are used to participate in the reaction, so as to improve the mechanical properties, water resistance and solvent resistance of the prepared film; organosilicon compounds are a special polymer compound, which has the characteristics of both inorganic compounds and organic compounds, and has many excellent properties such as low temperature resistance, aging resistance, hydrophobicity, organic solvent resistance, radiation resistance and the like; acrylic acid has good water resistance and weather resistance; polyurethane resin has good hydrophilicity and excellent coating performance.
[0014] During the film-forming process of the coating of the present application, the molecules of the organosilicon hybrid modified epoxy resin and the acrylic acid modified polyurethane resin will not interpenetrate or form a cross-linked network structure, and the adhesion between the epoxy resin and the substrate can be fully exerted. Therefore, the organosilicon hybrid modified epoxy resin and the acrylic acid modified polyurethane resin work together to improve the adhesion, weather resistance, salt spray resistance, and solvent resistance of the film formed by the water-based coating.
[0015] However, the two matrix resins, epoxy resin modified by organosilicon hybrid and polyurethane resin modified by acrylic acid, only interact with each other through physical action. After film formation, the mechanical strength (such as hardness, fracture strength, etc.) of the film still needs to be further improved. The applicant of the present application has found through research that if hollow glass microspheres with different particle sizes are added to the coating system of the present application, the mechanical strength of the coating after film formation can be significantly improved. Some large-particle hollow glass microspheres will float to the surface of the coating system, which is beneficial to the improvement of the surface gloss after film formation; at the same time, in the coating system, small-particle hollow glass microspheres will absorb some inorganic fillers such as rust-proof pigments and color fillers due to their large specific surface area, and these inorganic fillers such as rust-proof pigments and color fillers adsorbed on the surface of hollow glass microspheres can have excellent mobility in the system during the drying film formation process by virtue of the "rolling ball effect" of hollow glass microspheres, and evenly distribute them on the film surface, and then give full play to the role of the filler (such as the anti-flash rust function of rust-proof pigments).
[0016] It should be noted that a single hollow glass microsphere is a perfect spherical structure, so the diameter can clearly indicate the particle size of a single hollow glass microsphere; since the hollow glass microspheres added to the coating of the present application are a mixture of hollow glass microspheres of different particle sizes, D is selected. 90 and D 50 To represent the distribution relationship between the large and small particles of the added hollow glass microspheres. 90 It is the particle size corresponding to when the cumulative percentage of hollow glass microspheres reaches 90%, in μm; D 50 It is the particle size corresponding to when the cumulative percentage of hollow glass microspheres reaches 50%, in μm. 90 / D 50 Indicates the closeness between the large and small particle sizes of hollow glass microspheres, D 90 / D 50 The smaller it is, the closer the particle size of the large hollow glass microspheres is to that of the small hollow glass microspheres. 90 / D 50 In the range of 1.5 to 3.0, the coating has good adhesion, weather resistance, salt spray resistance and solvent resistance after film formation.
[0017] In the embodiment of the present application, the solid content of the organosilicon-modified epoxy resin is ≥55wt%; the viscosity at 25°C is 2000-15000cps; the density is 1.0-1.3g / cm 3 ; pH is 6.0-10.0. The paint film obtained by selecting the organosilicon-modified epoxy resin also has excellent anti-flash rust performance and quick drying properties.
[0018] In the embodiment of the present application, the acrylic modified polyurethane resin has a solid content of ≥40 wt %; a viscosity of 10 to 2000 cps at 25° C.; and a density of 1.0 to 1.3 g / cm 3 ; pH is 6.0-10.0. The paint film obtained by selecting the acrylic modified polyurethane resin also has excellent quick-drying properties.
[0019] In the embodiment of the present application, the hollow glass microspheres also satisfy: 1.5≤(D v95 / D v50 ≤3.5.D v95 It is the particle size corresponding to the cumulative volume percentage of hollow glass microspheres reaching 95%, in μm; D v50 is the particle size corresponding to the cumulative volume percentage of hollow glass microspheres reaching 10%, in μm; particle size distribution (D v95 / D v50 The larger the value, the larger the proportion of large-particle hollow glass microspheres. As the proportion of large-particle hollow glass microspheres increases, the mechanical strength of the coating after film formation will decrease, and the anti-rust pigments and pigments adsorbed on the small-particle hollow glass microspheres will decrease accordingly, and the anti-flash rust performance of the film will also show a downward trend; however, if the proportion of small-particle hollow glass microspheres is too large, it will cause the hollow glass microspheres in the coating system to agglomerate, forming larger aggregates that cannot migrate to the surface of the film during the film formation process to play their role. The particle size distribution of the hollow glass microspheres is within the scope of this application, and the hollow glass microspheres are evenly dispersed in the system. After the coating is formed into a film, it not only has excellent adhesion, weather resistance, salt spray resistance, and solvent resistance, but also has excellent anti-flash rust performance.
[0020] In the embodiment of the present application, the aqueous thickener includes at least one of cellulose, polyacrylate organic matter, polyurethane organic matter, and inorganic thickener. When the aqueous thickener is selected from the aqueous multifunctional thickener 402 (compounded with a variety of high-performance organic and inorganic substances) of Suzhou Pengcheng Material Technology Co., Ltd., the prepared coating has a more excellent anti-flash rust performance after film formation.
[0021] In an embodiment of the present application, the antirust pigment comprises at least one of zinc phosphate, aluminum tripolyphosphate, and a composite antirust pigment. The addition of the antirust pigment can significantly improve the antirust performance of the coating and improve the weather resistance of the coating. When the antirust pigment is the 3502 composite antirust pigment of Suzhou Pengcheng Material Technology Co., Ltd., the prepared coating has a more excellent anti-flash rust performance after film formation.
[0022] In an embodiment of the present application, the average particle size D of the pigment filler is less than 30 μm.
[0023] In an embodiment of the present application, the pigment filler includes at least one of titanium dioxide, iron oxide, carbon black, talcum powder, mica powder, silicon carbide, and barium sulfate.
[0024] In the embodiment of the present application, the wetting and dispersing agent is a high molecular polymer containing pigment affinity groups. Dispersants are used to disperse pigments. Dispersants need to have adsorption force with pigments. Therefore, the molecular structure of the dispersant needs to have groups with strong attraction to the pigment surface, that is, groups that are "affinity" with the pigment. For example, if it is a carbon black pigment, the dispersant structure needs to have aromatic rings, amino groups and other groups, which have a strong surface force with the carbon black; if it is an organic pigment, most of them are polycyclic compounds, so aromatic rings and other groups are also needed in the dispersant structure. Dispersants with pigment affinity groups can be more closely combined with pigments to make the dispersion system more stable. This combination is the so-called anchor combination. Dispersants with pigment affinity groups are generally more selective, that is, blue can only be used for blue, and the corresponding dispersants are used for other colors. Conventional wetting and dispersing agents in the field can be used in this application. In this application, according to the specific selection of pigments and fillers, wetting and dispersing agents containing corresponding groups are selected.
[0025] In an embodiment of the present application, the film-forming aid includes at least one of alcohol ether and alcohol ester solvents.
[0026] In an embodiment of the present application, the defoaming agent includes at least one of an organosilicon defoaming agent, an ether defoaming agent, and a mineral oil defoaming agent.
[0027] In an embodiment of the present application, the anti-settling aid includes at least one of bentonite, fumed silica, and cellulose.
[0028] In an embodiment of the present application, the pH adjuster includes at least one of ammonia water, N,N-dimethylethanolamine (DMEA), and 2-amino-2-methyl-1-propanol (such as the multifunctional amine auxiliary agent AMP-95 produced by Angus Company).
[0029] In an embodiment of the present application, the substrate wetting agent includes ethylene oxide adducts, polyether silicones and non-ionic fluorocarbon polymer compounds.
[0030] The present application also protects a method for preparing the above-mentioned modified water-based coating, comprising the following steps:
[0031] S1. Pre-dispersion
[0032] Evenly mix part of the organosilicon-modified epoxy resin, pH regulator, wetting and dispersing agent, defoaming agent, anti-settling aid, film-forming aid and part of water to obtain a pre-dispersion liquid;
[0033] S2. Preparation of slurry
[0034] Add anti-rust pigment, hollow glass microspheres, and pigment fillers to the pre-dispersed liquid obtained in step S1 and disperse to obtain a slurry;
[0035] S3. Preparation of modified coating
[0036] The acrylic modified polyurethane resin, the remaining silicone modified epoxy resin and the remaining water are added to the slurry obtained in step S2, and after mixing and dispersing, an aqueous thickener is added and dispersed to obtain the modified water-based coating.
[0037] The amount of epoxy resin added in step S1 can be 1 / 4 to 1 / 2 of the total weight of the epoxy resin in the coating, and more preferably 1 / 3.
[0038] The amount of water added in step S1 can be 2 / 3 to 3 / 4 of the total weight of water added to the coating.
[0039] The mixing speed in step S1 is 600-1500 r / min; during the dispersion in step S2, the stirring speed is 1500-2500 r / min, and the time taken to disperse to uniformity is in the range of 20-30 min; during the dispersion in step S3, the stirring speed is 600-2500 r / min, and the time taken to disperse to uniformity is in the range of 20-30 min.
[0040] The application of the modified water-based paint in the preparation of containers, steel structures, mechanical equipment, and transportation vehicles is also within the protection scope of the present application. The modified water-based paint can be widely used as a primer or a primer-top paint.
[0041] Compared with the prior art, the beneficial effects of this application are:
[0042] The coating of the present application is mainly composed of an epoxy resin modified by a silicone hybrid, which is further mixed and modified with an acrylic acid-modified polyurethane resin, so that the coating has good adhesion, weather resistance, salt spray resistance, and solvent resistance after film formation; hollow glass microbeads with different particle sizes are also added, which can significantly improve the mechanical strength of the coating after film formation, and work together with the anti-rust pigments in the coating system to improve the anti-flash rust performance of the coating after film formation. DETAILED DESCRIPTION
[0043] To better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific examples, but the examples do not limit the present application in any form. Unless otherwise specified, the reagents, methods and equipment used in the present application are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the present application are commercially available.
[0044] The following raw materials are selected in the examples of this application:
[0045] Silicone modified epoxy resin : Viscosity at 25°C is 5000cps, pH is 7.0, solid content is 58wt%, density is 1.06g / cm 3 ;
[0046] Acrylic modified polyurethane resin : Viscosity at 25°C is 50cps, pH is 8.0, solid content is 45wt%, density is 1.07g / cm 3 ;
[0047] Anti-rust pigment :
[0048] 1#: composite anti-rust pigment 3502, purchased from Suzhou Pengcheng Material Technology Co., Ltd.;
[0049] 2#: Zinc phosphate, ZP60, purchased from Guangxi Kelifang New Materials Co., Ltd.;
[0050] Pigments and fillers:
[0051] Titanium dioxide: 2500 mesh, commercially available;
[0052] Talc: 800 mesh, commercially available;
[0053] Barium sulfate: 3000 mesh, commercially available;
[0054] Wetting and dispersing agents : TEGO-755W, purchased from Evonik Chemicals, Germany;
[0055] Film-forming aids : Dipropylene glycol butyl ether (DPNB), purchased from Dow Chemical;
[0056] Defoaming agent :
[0057] 1#: polyether siloxane copolymer, TEGO AIREX901W, purchased from Evonik Chemicals, Germany;
[0058] 2#: mineral oil defoamer, TCB-1, purchased from Datian Chemical;
[0059] Anti-settling agent : Fumed silica, 300, purchased from Evonik;
[0060] pH Adjusters : N,N-dimethylethanolamine (DMEA), commercially available;
[0061] Water-based thickener :
[0062] 1#: water-based multifunctional thickener, 402, purchased from Suzhou Pengcheng Materials Technology Co., Ltd.;
[0063] 2#: Bentonite: commercially available;
[0064] Substrate wetting agent : Polyether modified siloxane, BYK349, purchased from BYK Chemical Company;
[0065] Hollow glass microspheres: See Table 1 for details;
[0066] Table 1 Parameters of hollow glass microspheres used in the examples and comparative examples
[0067] D(μm) <![CDATA[D 90 / D 50 ]]> <![CDATA[(D v95 ) / D v50 ]]> 1# 30 2.0 2.0 2# 30 1.5 2.0 3# 30 3.0 2.0 4# 30 2.0 1.5 5# 30 2.0 3.0 6# 30 4.0 1.5 7# 30 2.0 4.0 8# 60 2.0 1.5 9# 30 1.0 1.5 10# 15 2.0 2.0
[0068] Note: In Table 1, D refers to the average particle size of hollow glass microspheres. The above particle size parameters in the table are obtained by laser particle size analyzer testing.
[0069] Examples 1 to 16
[0070] The present application provides a series of modified water-based coatings. The composition of the coating raw materials is shown in Table 2 and Table 3. The preparation method comprises the following steps:
[0071] S1. Pre-dispersion
[0072] According to the raw material composition in Tables 2 and 3, 1 / 3 weight of organosilicon-modified epoxy resin, pH adjuster, wetting dispersant, defoamer, anti-settling aid, film-forming aid, and 2 / 3 weight of water were mixed evenly to obtain a pre-dispersion liquid;
[0073] S2. Preparation of slurry
[0074] Add anti-rust pigment, hollow glass microspheres (specific parameters are shown in Table 1), and pigment fillers to the pre-dispersed liquid obtained in step S1 and disperse to obtain a slurry;
[0075] S3. Preparation of modified coating
[0076] The acrylic modified polyurethane resin, the remaining silicone modified epoxy resin and the remaining water are added to the slurry obtained in step S2, and after mixing and dispersing, an aqueous thickener is added and dispersed to obtain the modified water-based coating.
[0077] Table 2 Raw material formula of modified water-based coating of Examples 1 to 5 (parts by weight, total weight is 100 parts)
[0078] Example 1 Example 2 Example 3 Example 4 Example 5 Silicone modified epoxy resin 20 25 30 35 40 Acrylic modified polyurethane resin 25 20 15 10 5 1# Anti-rust pigment 10 8 6 2 15 Pigments and Fillers-Titanium Dioxide 20 20 20 30 15 Wetting and dispersing agents 1.5 1.5 1.5 0.5 2.5 1# Hollow glass microsphere 1 2 3 3.5 0.5 Film-forming aids 4 3 3 1 2 1# Defoamer 0.3 0.3 0.3 0.5 0.1 Anti-settling agent 0.5 0.5 0.5 0.5 2.5 pH Adjusters 0.3 0.5 0.7 0.9 1.2 1# Water-based thickener 2.5 2.0 1.5 1.0 1.0 Substrate wetting agent 0.5 0.5 0.5 0.1 1.0 Deionized water margin margin margin margin margin
[0079] Table 3 Raw material formula of modified water-based coating of Examples 6 to 16 (parts by weight, total weight is 100 parts)
[0080]
[0081]
[0082] Comparative Example 1
[0083] This comparative example provides a water-based coating, which is prepared according to the method of Example 1, and is different from Example 1 in that hollow glass microspheres are not added.
[0084] Comparative Example 2
[0085] This comparative example provides a water-based coating, which is prepared according to the method of Example 1. The difference from Example 1 is that 9# hollow glass microspheres are added. The D 90 / D 50 Too small.
[0086] Comparative Example 3
[0087] This comparative example provides a water-based coating, which is prepared according to the method of Example 1. The difference from Example 1 is that 6# hollow glass microspheres are added. The D 90 / D 50 Too big.
[0088] Comparative Example 4
[0089] This comparative example provides a water-based coating, which is prepared according to the method of Example 1. The difference from Example 1 is that 8# hollow glass microspheres are added, and the average particle size of the hollow glass microspheres in this group of hollow glass microspheres is too large.
[0090] Comparative Example 5
[0091] This comparative example provides a water-based coating, which is prepared according to the method of Example 1. The difference from Example 1 is that hollow glass microspheres are not added to the formula. The preparation method of step S1 includes the following steps:
[0092] The raw materials of Example 1 were used to prepare a coating matrix according to the method of Example 1 in patent CN105131778A; then 0.3 parts of pH regulator, 1.5 parts of wetting dispersant, 0.3 parts of defoamer, 0.5 parts of anti-settling aid, 4 parts of film-forming aid and water were added and mixed evenly to obtain a pre-dispersion liquid;
[0093] The remaining steps are the same as those in Example 1, that is, in this comparative example, a cross-linked structure exists in the water-based coating matrix.
[0094] Performance Testing
[0095] The water-based coating obtained in the above examples and comparative examples is uniformly applied to the substrate required by the standard, and water is added to dilute it to a suitable viscosity when necessary. The treatment of the substrate should meet the requirements of the following relevant standards, wherein the 24h hardness cold-rolled steel plate is cured under standard conditions of 23°C (±2) and 50% (±5) relative humidity. Except for the surface drying time, actual drying time, and 24h hardness, all others are cured for 7 days. The performance after film formation is characterized, and the specific test items, test methods and results are as follows:
[0096] 1. Hardness: Tested in accordance with GB / T 6739-2006;
[0097] 2.60° gloss: tested in accordance with the standard GB / T 9754-2007;
[0098] 3. The surface drying time (min), actual drying time (h), water resistance (h), salt spray resistance (h), and adhesion (pull-off method) tests are conducted in accordance with the standard "HG / T 5176-2017";
[0099] 4. Impact resistance (cm): Tested in accordance with the standard "GB 1732-2020";
[0100] 5. The test method for anti-flash rust is to apply the paint film on the cold-rolled steel plate with a wet film thickness of 100μm, and then place it in a closed water tank with a humidity greater than 90%, and observe the time when flash rust appears on the paint film.
[0101] Table 4 Test results of water-based coatings obtained from the embodiments and comparative examples
[0102]
[0103] From the above results we can see that:
[0104] After the modified water-based coating of the present application is formed into a film, the comprehensive performance is excellent, among which the surface drying time is within 10 minutes, and can be as low as 8 minutes; the actual drying time is within 8 hours, and can be as low as 5 hours; the 24-hour hardness can reach H grade; the water resistance is all above 400 hours, and can be as high as 600 hours; the salt spray resistance is all above 500 hours, and can be as high as 1000 hours; the glossiness is all above 50, and can be as high as 85; the adhesion is all above 5MPa, and can be as high as 6MPa; the impact resistance is all above 70cm, and can be as high as 80cm.
[0105] The results of Examples 1 to 5 show that the modified water-based coating prepared when the raw materials are used in the above-mentioned dosage range has excellent comprehensive properties after film formation.
[0106] The results of Example 1 and Example 6 show that when the 3502 composite anti-rust pigment produced by Suzhou Pengcheng Material Technology Co., Ltd. is used, the prepared coating has even better anti-flash rust performance after film formation.
[0107] The results of Example 1, Examples 7-8, and Examples 13-14 show that conventional pigments, fillers, defoamers, etc. in the art can be used in the coating system of the present application, with little effect on the coating and the performance after film formation.
[0108] The results of Example 1, Examples 9 to 10, and Comparative Examples 2 to 4 show that a paint film with excellent comprehensive performance can be prepared only when the particle size and distribution of the hollow glass microspheres are within the above-mentioned appropriate range of the present application.
[0109] The results of Example 1 and Examples 11 to 12 show that suitable volume distribution of hollow glass microspheres can further improve the anti-flash rust performance of the prepared paint film.
[0110] In Comparative Example 1, hollow glass microspheres were not added, and the hardness and impact resistance of the obtained water-based paint after film formation were significantly worse than those of the embodiments of the present application. The results of Comparative Examples 2 to 4 show that the addition of hollow glass microspheres of appropriate particle size can prepare a paint film with excellent comprehensive performance.
[0111] In Comparative Example 5, there is a cross-linked structure between the resin matrix, resulting in the coating having significantly lower adhesion after film formation than the various embodiments of the present application.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A modified water-based coating, characterized in that: The composition comprises the following components in parts by weight: 20-40 parts of silicone modified epoxy resin; 5-25 parts of acrylic acid modified polyurethane resin; 2~15 parts of anti-rust pigment; Hollow glass microspheres 0.5~3.5 parts; 15~30 parts of pigments and fillers; Wetting and dispersing agent 0.5~2.5 parts; 1~4 parts of film-forming aid; Defoaming agent 0.1~0.5 parts; 0.5~2.5 parts of anti-settling agent; 0.3~1.5 parts of pH adjuster; 0.8~3.0 parts of water-based thickener; 0.1~1.0 part of substrate wetting agent; 5~20 parts water; The average particle size D of the hollow glass microspheres is less than 40 μm, and the particle size distribution D of the hollow glass microspheres is 90 / D 50 is 1.5~3.0; the hollow glass microspheres satisfy: 1.5≤D v95 / D v50 ≤3.5; the average particle size of the pigment filler D<30μm; the anti-rust pigment is selected from at least one of the composite anti-rust pigment 3502 and zinc phosphate ZP60.
2. The modified water-based coating according to claim 1, characterized in that: The organosilicon-modified epoxy resin has at least one of the following characteristics: a) Viscosity at 25°C is 2000~15000cps; b) Density is 1.0~1.3g / cm 3 ; c) pH 6.0~10.0; d) Solid content ≥55wt%.
3. The modified water-based coating according to claim 1, characterized in that: The acrylic modified polyurethane resin has at least one of the following characteristics: a) Viscosity at 25°C is 10~2000cps; b) Density is 1.0~1.3g / cm 3 ; c) pH 6.0~10.0; d) Solid content ≥40wt%.
4. The modified water-based coating according to claim 1, characterized in that: The aqueous thickener includes at least one of cellulose, polyacrylate organic matter, polyurethane organic matter, and inorganic thickener.
5. The modified water-based paint according to claim 1, characterized in that: Meet at least one of the following characteristics: a) the wetting and dispersing agent is selected from high molecular polymers containing pigment affinity groups; b) the film-forming aid comprises at least one of alcohol ether and alcohol ester solvents; c) the defoamer comprises at least one of an organosilicon defoamer, an ether defoamer and a mineral oil defoamer; d) the anti-settling aid comprises at least one of bentonite, fumed silica and cellulose; e) the pH adjuster comprises at least one of ammonia water, N,N-dimethylethanolamine and 2-amino-2-methyl-1-propanol; f) the substrate wetting agent comprises at least one of ethylene oxide adducts, polyether silicones and non-ionic fluorocarbon polymer compounds; g) The pigment and filler include at least one of titanium dioxide, iron oxide, carbon black, talcum powder, mica powder, silicon carbide and barium sulfate.
6. The method for preparing the modified water-based coating according to any one of claims 1 to 5, characterized in that: The steps include: S1. Pre-dispersion Evenly mix part of the organosilicon-modified epoxy resin, pH regulator, wetting and dispersing agent, defoaming agent, anti-settling aid, film-forming aid and part of water to obtain a pre-dispersion liquid; S2. Preparation of slurry Add anti-rust pigment, hollow glass microspheres, and pigment fillers to the pre-dispersed liquid obtained in step S1 and disperse to obtain a slurry; S3. Preparation of modified coating The acrylic modified polyurethane resin, the remaining silicone modified epoxy resin and the remaining water are added to the slurry obtained in step S2, and after mixing and dispersing, an aqueous thickener is added and dispersed to obtain the modified water-based coating.
7. Use of the modified water-based coating according to any one of claims 1 to 5 in the preparation of containers, steel structures, mechanical equipment, and transportation vehicles.
Citation Information
Patent Citations
Water-borne intermediate coating containing epoxy-organic silicon resin modified polyurethane-acrylic aqueous dispersion
CN105131778A
Environmentally friendly abrasion-resistant anticorrosive coating and preparation method thereof
CN106118360A
Quickly-cured solvent-scrubbing-resistant primer-topcoat anticorrosive paint and preparation method thereof
CN114836103A